Implementation of Pancasila on Bromo Prewedding Flare Case - Lyra Salsabiela; Jihan Safhira Sani; Lasrim Pardosi; Lestari Simanjuntak; Regita Yolanda Br Sinulingga; Risyanda Aulia Putri; Thea Erin Kristy Br Ginting Suka (LPPM UIKA Bogor, 2023)
The forest fires that occurred at Mount Bromo due to tourists' carelessness in lighting flares during pre-wedding photoshoots are concerning issues that necessitate in-depth analysis. This article explores the issue of the Mount Bromo fire, including its environmental impact, the risk of fire, and the ensuing social and economic impact. This article analyzes the Mount Bromo fire case in the context of Pancasila ethical values, emphasizing the importance of applying these values in everyday life. The research methodology involved a qualitative and descriptive approach using the literature study method, with data collected from various sources about the fire and its relation to the application of Pancasila values. This study endeavors to explore the application of Pancasila values in pre-wedding photoshoot scenarios that cause fires on Mount Bromo, and how implementing these values can raise social responsibility and environmental awareness. Additionally, this article illuminates the measures taken to tackle these issues and promote sustainability in Indonesia, a nation abundant in natural beauty.